Unwinding the spiral of silence in rural America: looking backward with stories to plan forward - Keller, Mary L.; Hansen, Kristiana; Shinker, J. J.; Landreville, Kristen D.; Cooper, Kathryn E.; Donaldson, Emily; Kim, Michelle; Paige, Ginger B.; Van Sandt, Anders (Frontiers in Climate, 2025)
IntroductionIn regions where climate change is perceived to be a controversial topic, people often self-silence rather than explore their concerns by speaking with others in their local social networks. The “spiral of silence” is a social feedback loop in which individuals are reluctant to speak about an issue because they believe they hold a minority opinion, leading to anxiety and fear, which prohibit action. Facilitating conversations about climate change is therefore a crucial step for researchers concerned with enhancing adaptive capacity. The goal of this paper is to provide a road map for engaging rural communities in conversations about their lived experiences with and local knowledge related to climate and water-related risks (e.g., drought). Our research focuses on unwinding the spiral of silence through community engagement to address the following questions: 1. How do rural Wyoming community members perceive recent climate conditions and water-related risks; and 2. How do rural Wyoming community members perceive and discuss future climate scenarios?MethodsOur first research question is addressed through analysis of results from a statewide survey, which are used to develop prompts for a scenario planning workshop to support the second research question. Our second research question is addressed through transcription and coding of recorded discussions and responses during and after participatory scenario planning workshops in key communities around the state.ResultsResults from the statewide survey indicate that respondents largely agree that all seasons are getting warmer than in the past and that drought is the dominant water risk of concern; however, there is uncertainty about community preparedness. Inclusion of prompts in our participatory scenario planning workshops that were aligned with statewide survey results allowed shared communication opportunities among community members and identified local knowledge of past drought events and associated adaptation strategies for the future.DiscussionOur mixed-method approach provides an example for unwinding the spiral of silence in rural communities experiencing challenges and impacts of climate change.